2012
DOI: 10.1111/j.2042-3306.2012.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

B‐mode andDoppler ultrasonography in pony mares with experimentally induced ascending placentitis

Abstract: SummaryReasons for performing study: Early, accurate diagnosis of ascending placentitis in mares remains a key challenge for successful treatment of the disease. Doppler ultrasonography has shown promise as a tool to diagnose pregnancy abnormalities and is becoming more available to equine clinicians. However, to date, no studies have prospectively compared this technique to standard B-mode measurement of the combined thickness of the uterus and placenta (CTUP). Objectives:The objective of the current study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
2
24
2
Order By: Relevance
“…We report normal reference ranges and demonstrate that regional uteroplacental thickness significantly increases with each trimester. Disruption of uteroplacental contact, a sign of placentitis and abnormal separation of the allantochorion from the endometrium, 41 was not seen in any of the successful pregnancies in Notes. Quantile regression threshold equations used to determine 95% confidence intervals.…”
Section: Discussionmentioning
confidence: 80%
“…We report normal reference ranges and demonstrate that regional uteroplacental thickness significantly increases with each trimester. Disruption of uteroplacental contact, a sign of placentitis and abnormal separation of the allantochorion from the endometrium, 41 was not seen in any of the successful pregnancies in Notes. Quantile regression threshold equations used to determine 95% confidence intervals.…”
Section: Discussionmentioning
confidence: 80%
“…In human medicine, alterations in the placenta (e.g., premature placental detachment) are detected by an increase in uterine resistance [42][43][44]. Bailey et al [11] recently induced placentitis in six pony mares, which was detected by increased CTUP within 3 days after inoculation. Although these mares were examined ultrasonographically at very regular intervals (12 hours for 5 days, 24 hours for 8 days, and 48 hours until delivery), Doppler ultrasonographic measurements of resistance index, PI, and total arterial blood flow did not reveal differences between the infected and uninfected mares.…”
Section: Abortion and Placentitismentioning
confidence: 97%
“…In human medicine, color Doppler sonography has become routine for the diagnostic evaluation of high-risk pregnancies [3][4][5]. Bollwein et al [6,7], Ousey et al [8,9], and Bailey et al [10,11] analyzed blood flow parameters during equine pregnancies. The Doppler sonographic studies illustrated a decrease in the peripheral blood flow resistance in the first weeks of pregnancy and an increase in uterine blood flow volume (BFV), especially in the last trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether there is any risk of foetal loss, endocrine profiling (Rossdale et al, 1991;Stawicki et al, 2002;Morris et al, 2007) and transrectal and transabdominal ultrasonography Bucca et al, 2005;Carrick et al, 2010;Löf et al, 2010) are frequently used, and are reported during late gestation, at around 8-10 months. Bailey et al (2012) also compared the ability of B-mode and Doppler ultrasonography to detect ascending placentitis in pony mares with experimentally induced disease.…”
Section: Introductionmentioning
confidence: 99%